N-alkyl functionalized squaraine dyes as fluorescent probes for the detection of serum albumins - Syniugina, A. T.; Chernii, S. V.; Losytskyy, M. Yu; Özkan, Hülya; Slominskii, Yu L.; Syniugin, A. R.; Pekhnyo, V. I.; Mokhir, Andriy; Yarmoluk, S. M. (Biopolymers and Cell, 2022)
Aim. Here we synthesize a series of benzoindolium squaraine dyes with N-substituents (SQ) and examine these dyes as fluorescent probes to detect serum albumins. Methods. Organic synthesis, fluorescent spectroscopy, absorption spectroscopy, fluorescent microscopy. Results. The spectral-luminescent properties of SQ dyes in the aqueous solution were investigated in the presence of bovine serum albumin (BSA), human serum albumin (HSA), equine serum albumin (ESA), ovalbumin (OVA), beta-lactoglobulin (BLG) and lysozyme (LYS), as well as in the presence of nucleic acid. The maxima of excitation spectra of the studied dyes in the buffer solution ranged within 623–673 nm, with the fluorescence emission maxima lying between 635 and 690 nm. All these dyes showed a similar increase in the fluorescence intensity with serum albumins and at the same time with the red shift up to 12 nm, which could point out the binding of the dyes to proteins. These dyes demonstrate a noticeably lower fluorescence intensity in the presence of OVA, BLG, and LYS, which structurally differ from serum albumins. The studied dyes gave no significant fluorescent response to the addition of nucleic acids. The equilibrium constants of dyes binding to BSA (K) were estimated as 3.0 ± 0.3x105 M-1 for SL-2411 and 2.4 ± 0.6x105 M-1 for SL-2412. Based on the relative values of K, we could suppose that the mechanism of dye-BSA binding is the interaction of the chromophore of the dye with the protein globule. It was shown that SL-2411 penetrates the cell membrane and distributes in the cytoplasm without co-localization with MitoTracker Green. Conclusion. These dyes could apply fluorescent spectroscopy for protein detection and potentially visualize cell components with minimum to no autofluorescence.
CRIS-Team Scopus Importer:2024-12-16
Keywords: absorptions spec-troscopy; fluorescence microscopy; fluorescent detection; fluorescent spectroscopy; serum albumins; squaraine dyes